PENGARUS UTAMAAN PENDIDIKAN DAMAI (PEACEFUL EDUCATION) DALAM PENDIDIKAN AGAMA ISLAM (Solusi Alternatif Upaya Deradikalisasi Pandangan Agama) - Eka Hendry (AT-TURATS, 2015)
One of the issues facing the contemporary world society is the increasing escalation of violence (including radicalism under the pretext of religion). At least, we can remember the events closest to the writing of this article i.e. bomb attacks in France and in Thamrin Jakarta. This phenomenon signifies that radicalism is continuing to grow and becoming a threat to modern society. It also has affected all parties in some way, and therefore all should take part in preventing such violent acts from occurring in the future. Among the institutions that have a role in suppressing radicalism under the name of religion is an educational institution, especially religious educational institutions. Ironically, the institution itself is still facing serious problems, including the issue of peace which has yet to be a mainstream premise of Islamic religious education. The themes of peace education are merely a fragmented material. This paper offers a principal concept of peace education and its practical forms developed from the Qur’an. Therefore, this paper is a review of the normative Islamic perspective on peace and conflict. Peace education is expected to shape the community (especially students) to be independent and literate with efforts of peace building and conflict resolution. The purpose of this article is to explore the Islamic perspective on peace, which can be developed in the instruction of Islamic education both in the school and madrasa.